The Effectiveness of Jigsaw Strategy in Geography Subject of Earth as Living Space Material - Siti Hadiyati Nur Hafida; Mohd Hairy Ibrahim; Siti Azizah Susilawati; Rahmat Riandi Suparno; Suharjo Suharjo; Wahyu Widiyatmoko (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2020)
The purpose of this study is to improve student learning in geography subjects at class X of MA Muhammadiyah Gantung Belitung Timur in academic year 2018/2019 using the Jigsaw strategy. The subject of the study was class X, amounting to 22 students. This research is a quasi-experimental research with pretest-posttest design. This study uses a control and experimental group. The conclusion of this research is the implementation of Jigsaw strategy can improve the effectiveness of students in learning geography in class X of MA Muhammadiyah Gantung Belitung Timur. This is consistent with the results of the N-Gain Test in the experimental group which has an average of 31.97 and the control group has an average of 12.52 therefore, the experimental group has a medium value and the control group shows a low value. N-Gain test data showed that the experimental group learning was more effective than the control group. Learning outcomes between the experimental group and the control group showed a difference, the control group had an average pre-test value of 60 and an average post-test of 65. The experimental group had an average score of 61.82 and the post-test -test 74.09. The experimental group had higher pre-test and post-test scores compared to the control group, therefore Ha was accepted while Ho was rejected, this shows that the use of jigsaw learning strategies in the experimental group was effective in increasing students' knowledge and understanding of earth material as the space of life.